Perception of Patients Knowledge Regarding the COVID-19 Pandemic Attending the Dental OPD of Dow Dental College - Siddiqui, Saad Uddin; Abrar, Syed Kashif; Kashmiri, Ziauddin; Mustafa, Muhammad; Nasir, Zeeshan; Nasir, Saqif (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To understand the patient's knowledge and perception of the COVID-19 pandemic and associated preventative measures. Methodology: A cross-sectional research was carried out among dental patients visiting the Dow Dental College Karachi OPD from August to October 2020. The questionnaire was developed in compliance with the COVID-19 community recommendations of the CDC and WHO. The estimated number of dental patients attending the dental OPD each month is 3200, thus using this as population size, the sample size computed was 344 by using open epi and retaining the power at 80%, the confidence interval at 95%, and the margin of error at 0.05 percent. Results: In total, 344 patients took part in the research. Regarding COVID-19 pandemic knowledge, most patients (317/344) thought that the most frequent signs and symptoms linked with COVID-19 are fever, fatigue, and a dry cough. The majority of them believed that wearing a mask 314/344, i.e., 91.2%, and washing their hands 324/344, i.e.,94.1% properly, was required to reduce the effects of COVID-19. Conclusion: The findings revealed that most participants had a strong understanding of COVID-19 as a pandemic. They demonstrated positive attitudes and excellent behaviors for avoiding disease infection transmission. Keywords: SARS-Cov-2; physical distancing; PPE Personal Protective Equipment; vaccines; pandemics